Ablation of Sphingosine 1-Phosphate Receptor Subtype 3 Impairs Hippocampal Neuron Excitability In vitro and Spatial Working Memory In vivo - Weth-Malsch, Daniela; Langeslag, Michiel; Beroukas, Dimitra; Zangrandi, Luca; Kastenberger, Iris; Quarta, Serena; Malsch, Philipp; Kalpachidou, Theodora; Schwarzer, Christoph; Proia, Richard L.; Haberberger, Rainer V.; Kress, Michaela (Frontiers in Cellular Neuroscience, 2016)
Understanding the role of the bioactive lipid mediator sphingosine 1-phosphate (S1P) within the central nervous system has recently gained more and more attention, as it has been connected to major diseases such as multiple sclerosis and Alzheimer's disease. Even though much data about the functions of the five S1P receptors has been collected for other organ systems, we still lack a complete understanding for their specific roles, in particular within the brain. Therefore, it was the aim of this study to further elucidate the role of S1P receptor subtype 3 (S1P3) in vivo and in vitro with a special focus on the hippocampus. Using an S1P3 knock-out mouse model we applied a range of behavioral tests, performed expression studies, and whole cell patch clamp recordings in acute hippocampal slices. We were able to show that S1P3 deficient mice display a significant spatial working memory deficit within the T-maze test, but not in anxiety related tests. Furthermore, S1p3 mRNA was expressed throughout the hippocampal formation. Principal neurons in area CA3 lacking S1P3 showed significantly increased interspike intervals and a significantly decreased input resistance. Upon stimulation with S1P CA3 principal neurons from both wildtype and S1P3−/− mice displayed significantly increased evoked EPSC amplitudes and decay times, whereas rise times remained unchanged. These results suggest a specific involvement of S1P3 for the establishment of spatial working memory and neuronal excitability within the hippocampus.